2021
DOI: 10.1177/01455613211028094
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Sudden Hearing Loss and Peripheral Facial Paralysis in a Patient With Covid-19

Abstract: Although peripheral facial paralysis and sudden sensorineural hearing loss are not as common as anosmia, they are reported neurological manifestations of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We present a 62-year-old, serologically COVID-19 positive woman with seventh and eighth nerve involvement showed electrophysiologically with Auditory Brainstem Response and electroneurography and radiologically with internal acoustic canal magnetic resonance imaging. This single case report suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 22 publications
(35 reference statements)
0
21
0
3
Order By: Relevance
“…Most patients with COVID-19-related SSNHL showed normal MRI findings, while some developed an intra-labyrinthine hemorrhage ( 7 , 13 ). Ozer et al reported a case of SSNHL with peripheral facial paralysis in a COVID-19 patient, suggesting a link between SSNHL and isolated facial paralysis ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most patients with COVID-19-related SSNHL showed normal MRI findings, while some developed an intra-labyrinthine hemorrhage ( 7 , 13 ). Ozer et al reported a case of SSNHL with peripheral facial paralysis in a COVID-19 patient, suggesting a link between SSNHL and isolated facial paralysis ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…Due to isolation of patients, telephone consultations were also used to provide an initial assessment of the patient's condition ( 13 ). Auditory brainstem response (ABR), otoacoustic emission, and electroneuronography were applied in a few studies ( 25 , 28 ). Two studies used a head-shaking test or video head impulse testing to identify vertigo ( 11 , 27 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although more evidence is yet to be found, the temporal relation between the AZCV exposure and the appearance of hearing loss and tinnitus a few days after the vaccination in all cases clearly points toward a likely association between the vaccine and the otologic symptoms. Many authors have considered a possible link between COVID-19 infection and SSHL [ 2 , 6 - 10 ]; however, as far as the author knows this is the first case series considering the possible association between a COVID-19 vaccine and inner ear damage, which could indeed have pathophysiology similar to that of the cases of SSHN secondary to COVID-19 infection. We display the audiometries of cases 1 and 5 since we believe them to be the most representative of the situation described by Tseng et al [ 12 ] (case 1) and the one described by Tsetsos et al [ 11 ] (case 5).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous reports have mentioned the possible link between COVID-19 infection and inner ear damage [2,[6][7][8][9][10]; however to the authors´ very best knowledge this is the first case series considering the possible association between AZCV (or any COVID-19 vaccine) and inner ear damage, and so far only two previous isolated single case reports of auditory symptoms related to the AZCV have been described, including one report of SSHL itself [11], and one report of tinnitus presumably associated to cochleopathy secondary to the vaccine [12]. To our best knowledge, this is the first report of a patient with vestibular symptoms related to the AZCV.…”
Section: Introductionmentioning
confidence: 99%